Beyond Compliance: Measuring The Economic Impact of Integrated Sustainability Reporting (ISR) on Firm Value and Stakeholder Trust in the Era of CSRD - Aritonang, Monica Christin; Sophia, Sophia; Ratnasari, Tri Dessy (International Journal of Economics (IJEC), 2025)
This qualitative study examines the economic impact of Integrated Sustainability Reporting (ISR) on firm value and stakeholder trust amid the evolving regulatory environment driven by the Corporate Sustainability Reporting Directive (CSRD). Unlike conventional compliance-based reporting, ISR integrates financial and non-financial disclosures to provide a holistic view of a firm’s sustainability performance. Through thematic analysis of documents and semi-structured interviews with corporate sustainability officers, investors, and regulatory experts, this research uncovers how ISR influences firm valuation and strengthens stakeholder relationships. The findings reveal that ISR enhances transparency and accountability, which fosters increased stakeholder trust and positively affects firm reputation and market perceptions. Consequently, firms adopting ISR benefit from improved access to capital and stronger engagement with stakeholders including customers, employees, and regulators. Challenges remain in harmonizing sustainability data and measuring outcomes comprehensively, yet the strategic value gained through ISR implementation surpasses these hurdles. This study highlights ISR’s role beyond mere regulatory compliance, positioning it as a critical tool for sustainable value creation and trust building in the CSRD era. The insights provide valuable implications for firms seeking to leverage integrated sustainability disclosures to achieve competitive advantage and long-term growth